REDUCING SIGN AND SYMPTOMS OF THE RISK OF VIOLENT BEHAVIOR IN SCHIZOPHRENIA PATIENTS THROUGH THERAPEUTIC WRITING - Audina, Sheren (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Schizophrenia is a common and widely encountered mental illness, characterized by perceptual disturbances and significant changes in behavior. Patients with schizophrenia have complex disorders, one of which is a disorder of the frontal lobe brain region which plays an important role in emotional experience and mood expression. This can cause individuals with schizophrenia to have difficulty controlling their emotions and moods, which can have an impact on the risk of violent behavior. The risk of violent behavior is vulnerable to behaviors that can be physically, emotionally, and/or sexually harmful to oneself or others. The purpose of this scientific work is to identify the application of de-escalation using therapeutic writing in reducing signs and symptoms of risk of violent behavior in patients with schizophrenia. Patient initials Mr. I, 27 years old and has a history of violent behavior of raging and hitting parents at home. Nursing action for the risk of violent behavior is given for 10 days with the application of de-escalation: therapeutic writing. This scientific work is written based on a case study using a signs and symptoms evaluation instrument developed by the Department of Mental Nursing, Faculty of Nursing Sciences, University of Indonesia. The results of the application of therapeutic writing on the patient showed a decrease in signs and symptoms of risk of violent behavior from a score of 12 to a score of 1. De-escalation therapy with therapeutic writing is expected to be applied as an alternative nursing action to reduce signs and symptoms of risk of violent behavior in patients.